Clinical features of patients with fungal infections caused by CARD9 deficiency: a literature review of case reports - Tang, Congchen; Liu, Yalan; Long, Jiangchao; Lv, Xiaoju (Frontiers in Cellular and Infection Microbiology, 2025)
Caspase recruitment domain containing protein 9 (CARD9) deficiency is an autosomal-recessive primary immunodeficiency disorder, undermines the body’s capacity to combat fungal infections. In recent years, the number of reported cases of fungal infections associated with CARD9 deficiency has been increasing. This study undertook a systematic review of case reports, incorporating 89 patients with CARD9 deficiency complicated by fungal infections. The findings demonstrated that the patient population predominantly consisted of young and middle-aged individuals (33.43 ± 19.12 years, range: 1-91), and the majority (52 patients, 58.43%) developed the disease during childhood or adolescence. Significant geographical variations were observed in the distribution of gene mutations. Specifically, the c.820dupG mutation was predominantly found in East Asia, while the c.865C>T mutation was primarily found North Africa. Regarding the clinical manifestations, the most frequently affected sites were the skin, central nervous system, and lymph nodes, and the principal fungal pathogens identified were Trichophyton and Candida. Correlation analysis indicated that c.883C>T increased the likelihood of Candida infection (p=0.008, OR=10.421, 95% CI 1.849-58.748), c.865C>T increased the probability of Trichophyton infection (p=0.038, OR=5.760, 95% CI 1.098-30.217) and dematiaceous fungi infection (p=0.005, OR=9.653, 95% CI 2.019-46.153). According to the types of mutations, nonsense mutation increased the risk of dematiaceous fungi infection (p=0.014, OR=6.212, 95% CI 1.453-26.556). Notably, a proportion of patients succumbed to the disease, and this was predominantly associated with infections of the central nervous system, blood system, and viscera. This underscores the importance of adequate antifungal therapy and long-term follow-up for patients with CARD9 deficiency-related fungal infections.